From Tradition to Liturgy: Exploration of Rodat Music in the Context of Catholic Church Music - Yohanes Ruswanto (Universitas Negeri Semarang, 2025)
Abstract Liturgical singing in local languages is increasingly rare in Eucharistic celebrations, particularly in forms that incorporate percussion-based accompaniment. This study aims to develop a new Javanese liturgical composition entitled Minulya to enrich musical expressions of praise and provide alternative accompaniment models rooted in local tradition. The work adopts the musical idiom and instrumentation of Rodat, a traditional performing art from Central Java. Using a qualitative approach and literature study, data were collected through textual analysis, observation, and interviews with Rodat artists in Bungkel Hamlet, Pucung Village, Bancak District, Semarang Regency. Musical materials, especially rhythmic patterns, were documented and transformed into notated compositions. Structural, musicological, and lyrical analyses were conducted to examine the resulting work. The findings demonstrate that integrating regional musical traditions into liturgical contexts expands creative possibilities and affirms the universal function of music in religious practice. The composition Minulya offers an alternative model of Javanese-language Eucharistic singing with percussion-based accompaniment, contributing to the preservation and contextualization of local culture in liturgical music.